(untitled) (Journal of Nematode Morphology and Systematics, 2012)
Tobrilonchulus novaezelandiae gen. n., sp. n. from New Zealand is particularly characterized by outer labial and cephalic sensilla arranged at the same level; stoma with one minute dorsal tooth, two ventrosublateral denticles and two drop-shaped sclerotizations; presence of gubernaculum; and long fl agelliform tail with caudal glands and spinneret. Tobriloides choii is redescribed on the basis of type specimens and fresh material collected in South Korea and China; particularly, new data are provided about the morphology of stoma and secretory-excretory system. Tobriloides camerunensis sp. n. from Cameroon is distinguished by shape of stoma, short cardia, number of supplements and tail shape. Onchulus fl agellatus sp. n. from Benin is distinguished by sexually dimorphic amphids, fi lamentous spermatozoa, supplements extending to the pharyngeal region and arranged in two sets, presence of gubernaculum, and short tail without caudal glands and spinneret. Limonchulus costaricanus sp. n. from Costa Rica is differentiated from other species of the genus by the presence of an organellum dorsale. Males of Stenonchulus troglodytes, described for the fi rst time, have spicules without distinct manubrium, with anteriorly directed projection and with arcuate conoid lamina; small and slender gubernaculum; and four midventral precloacal sensilla. Type specimens of Pseudonchulus inermis, Paronchulus straticauda and Onchulus fi licaudatus are redescribed. A cladistic analysis of 13 species representing seven genera of Onchulidae is provided on the base of published and updated morphological data. The genus Paronchulus is synonymised with Onchulus, the genus Pseudonchulus is synonymised with Kinonchulus, and Pseudonchulus inermis is synonymised with Kinonchulus sattleri.